BDNF is required for seizure-induced but not developmental up-regulation of KCC2 in the neonatal hippocampus. (January 2015) - Puskarjov, Martin; Ahmad, Faraz; Khirug, Stanislav; Sivakumaran, Sudhir; Kaila, Kai; Blaesse, Peter
Abstract: A robust increase in the functional expression of the neuronal K–Cl cotransporter KCC2 during CNS development is necessary for the emergence of hyperpolarizing ionotropic GABAergic transmission. BDNF-TrkB signaling has been implicated in the developmental up-regulation of KCC2 and, in mature animals, in fast activity-dependent down-regulation of KCC2 function following seizures and trauma. In contrast to the decrease in KCC2 expression observed in the adult hippocampus following trauma, seizures in the neonate trigger a TrkB-dependent up-regulation of neuronal Cl − extrusion capacity associated with enhanced surface expression of KCC2. Here, we show that this effect is transient, and impaired in the hippocampus of Bdnf −/− mice. Notably, however, a complete absence of BDNF does not compromise the increase in KCC2 protein or K-Cl transport functionality during neuronal development. Furthermore, we present data indicating that the functional up-regulation of KCC2 by neonatal seizures is temporally limited by calpain activity. This article is part of the Special Issue entitled 'GABAergic Signaling in Health and Disease'. Highlights: BDNF has been implicated in KCC2 up-regulation during neuronal development. Seizures induce age-dependent changes in KCC2 expression and function. We show that developmental up-regulation of KCC2 is unaffected in Bdnf −/− hippocampi. By contrast, lack of BDNF impairs KCC2 activation triggered by neonatal seizures.